2016
DOI: 10.1117/12.2218645
|View full text |Cite
|
Sign up to set email alerts
|

Selective removal of dental composite with a diode-pumped Er:YAG laser

Abstract: Selective removal of dental composite with high precision is best accomplished using lasers operating at high pulse repetition rates focused to a small spot size. Conventional flash-lamp pumped Er:YAG lasers are poorly suited for this purpose, but new diode-pumped Er:YAG lasers have become available operating at high pulse repetition rates. The purpose of this study was to compare the ablation rates and selectivity of enamel and composite for a 30 W diode-pumped Er:YAG laser operating with a pulse duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The characterization of the transmission behavior of dental materials for different laser wavelengths, as performed in the study at hand, forms the basis for the development of some new laser applications. An example for such applications is the selective removal of a filling material, for example, in case of a defective filling, without harming the tooth substance below . The filling material should exhibit very high transmission for a specific laser wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…The characterization of the transmission behavior of dental materials for different laser wavelengths, as performed in the study at hand, forms the basis for the development of some new laser applications. An example for such applications is the selective removal of a filling material, for example, in case of a defective filling, without harming the tooth substance below . The filling material should exhibit very high transmission for a specific laser wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published regarding the use of lasers to remove composite from tooth surfaces. [4][5][6][7][8][9][10][11][12][13][14][15] Studies investigating CO 2 lasers for the uses of removing either composite, enamel and dentin found that it can be accomplished with minimal impact to the pulp if operated at 9.3 and 9.6-μm wavelengths. A clinical study investigating the pulpal response to the same carbon dioxide laser used in this study demonstrated that the laser can be used safely to ablate enamel without pulpal damage.…”
Section: Introductionmentioning
confidence: 99%
“…Diode pumped solid-state (DPSS) Er:YAG lasers are now available operating with pulse repetition rates as high as 1-2 kHz and initial studies have been carried out demonstrating their utility for the ablation of dental hard tissues and bone [22][23][24]. We have explored using this system for the removal of dental caries and composites [25][26][27].…”
mentioning
confidence: 99%